A Wohlfahrtiimonas chitiniclastica with a novel type of blaVEB–1-carrying plasmid isolated from a zebra in China - Guan, Jiayao; Zhou, Wei; Guo, Jingyi; Zheng, Lin; Lu, Gejin; Hua, Fuyou; Liu, Mingwei; Ji, Xue; Sun, Yang; Zhu, Lingwei; Guo, Xuejun (Frontiers in Microbiology, 2023)
Background Wohlfahrtiimonas chitiniclastica is an emerging fly-borne zoonotic pathogen, which causes infections in immunocompromised patients and some animals. Herein, we reported a W. chitiniclastica BM-Y from a dead zebra in China. Methods The complete genome sequencing of BM-Y showed that this isolate carried one chromosome and one novel type of blaVEB-1-carrying plasmid. Detailed genetic dissection was applied to this plasmid to display the genetic environment of blaVEB-1. Results Three novel insertion sequence (IS) elements, namely ISWoch1, ISWoch2, and ISWoch3, were found in this plasmid. aadB, aacA1, and gcuG were located downstream of blaVEB-1, composing a gene cassette array blaVEB-1-aadB-aacA1-gcuG bracketed by an intact ISWoch1 and a truncated one, which was named the blaVEB-1 region. The 5ˊ-RACE experiments revealed that the transcription 2 This is a provisional file, not the final typeset article start site of the blaVEB-1 region was located in the intact ISWoch1 and this IS provided a strong promoter for the blaVEB-1 region. Conclusions The spread of the blaVEB-1-carrying plasmid might enhance the ability of W. chitiniclastica to survive under drug selection pressure and aggravate the difficulty in treating infections caused by blaVEB-1-carrying W. chitiniclastica. To the best of our knowledge, this is the first report of the genetic characterization of a novel blaVEB-1-carrying plasmid with new ISs from W. chitiniclastica.